Joint Forest Planning and Management in Uttar Kannada District, Karnataka - Gaonkar, D. S.; Gowda, B. Shivanna (Indian Forester, 2000)
In pursuance of National Forest Policy, 1988 and su,bsequent Govt. of India instructions, 1990, Joint Forest Management has been taken up in Karnataka. The present paper outlines the work done in Uttar Kannda District thereof. It is a large area, divided into three distinct zones, consisting of a number of well populated villages. These are moderate to heavily dependent on forests degraded to a great extent and have been divided into Areca, paddy and livestock systems each having its peculiarities. Previous working of Social Forestry has been reviewed and found deficient. Forest Management problems of each zone have been analysed and projects taken up briefly outlined. The working of Joint Forest Management, the Village Forest Committees formed, their working defined, sharing of forest produce from managed areas indicated, other amenities, services and facilities provided to village communities have been briefly touched upon as also participation of local popUlation in the Management and microplanning of areas to attain success have been defined along with related subjects. The authors conclude that peoples' participation has to be viewed as a movement towards humanization and democratisation for attaining equity and sustain ability, particularly so for development and conservation of forests.